Nostalgia in reviving interior spaces the case of the Henry Hotel Manila - Joloyohoy, Kirsten S.; Taluban, Joseph G., Jr. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
The study aimed to learn more about nostalgia –– a complex and positive emotion affecting the human psyche that evokes positive sentimental emotions and plays a significant role in interior design when applied as a design strategy. The research attempted to correlate nostalgia to spatial elements and know its impact on the users of a space –– focusing on how memory, Human Behavior Theory, and emotional design came together as a foundation for nostalgia-based interior design. The study utilized a qualitative research case study, with The Henry Manila being selected as the area of the study. Respondents, chosen through purposive sampling, consisted of five (5) participants for the focus group discussion, and the designer of The Henry Manila himself was interviewed. Data collected were subjected to thematic analysis: results indicated that through the use of mood, lighting, color, and by simply enhancing what was already there, elements of the design remained authentic and familiar, which kept it relatable and nostalgic for guests. This nostalgia was found to have increased their engagement and sense of identity within the space, adding to the level of comfort, well-being, and productivity they experienced, despite it setting high expectations which slightly decreased the respondents’ satisfaction with the space when it was unable to perfectly replicate what they remembered in their memories. The study’s findings can give interior designers insight on how nostalgia has the potential to create spaces that are emotionally resonant, meaningful, and conducive to human well-being, which can be especially useful in adaptive reuse and in the promotion of sustainability and heritage values.
Thesis
Bibliography: pages 63-68.
Keywords: Nostalgia -- Philippines; Interior decoration -- Philippines